Insight into Concept and Progress on Pharmaceutical Co-Crystals: An Overview - Vemuri, Venkata Deepthi; Lankalapalli, Srinivas (Indian Journal of Pharmaceutical Education and Research, 2019)
Pharmaceutical co-crystals have conferred significant recognition in recent past as a new solid form by virtue their capability to modulate physicochemical properties of Active Pharmaceutical Ingredient (API). Nevertheless, pharmaceutical progress of cocrystals could be provocation, the requirement for high-throughput screening methods and the techniques capable of co-crystal production in industrial scale still hamper the co-crystal used by industries. In this review, well ordered overview of pharmaceutical co-crystal is provided, with focus on role of supramolecular chemistry, co-crystal design strategies, preparation methods, physicochemical property studies, mechanism of solubility enhancement, evaluation techniques. In the present commentary, the impact of choosing appropriate process design and formulation on translational challenges has been discussed. Eventually, a short outline of applications and marketed drug products of pharmaceutical co-crystal drug substance is also described.
Keywords: Co-crystals; Crystal engineering; Physicochemical properties; Co-crystallization; Translational challenges